2001
DOI: 10.1103/physrevb.64.024424
|View full text |Cite
|
Sign up to set email alerts
|

Theory of transition temperature of magnetic double perovskites

Abstract: We formulate a theory of double perovskite coumpounds such as Sr2FeReO6 and Sr2FeMoO6 which have attracted recent attention for their possible uses as spin valves and sources of spin polarized electrons. We solve the theory in the dynamical mean field approximation to find the magnetic transition temperature Tc. We find that Tc is determined by a subtle interplay between carrier density and the Fe-Mo/Re site energy difference, and that the non-Fe same-sublattice hopping acts to reduce Tc. Our results suggest t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 14 publications
8
79
0
Order By: Relevance
“…In the metallic SFMO and BFMO systems, the DE-like interaction becomes operative due to the degenerate Fe and Mo t 2g ↓ states near E F . In the DE mechanism, the magnetic transition temperature T C is proportional to the hopping strength, i.e., the bandwidth of the itinerant t 2g ↓ states [26]. The observed correlation between T C and the estimated bandwidth in metallic double perovskites provides evidence for the operation of the DE-like interaction [18].…”
Section: +mentioning
confidence: 90%
“…In the metallic SFMO and BFMO systems, the DE-like interaction becomes operative due to the degenerate Fe and Mo t 2g ↓ states near E F . In the DE mechanism, the magnetic transition temperature T C is proportional to the hopping strength, i.e., the bandwidth of the itinerant t 2g ↓ states [26]. The observed correlation between T C and the estimated bandwidth in metallic double perovskites provides evidence for the operation of the DE-like interaction [18].…”
Section: +mentioning
confidence: 90%
“…For a general direction of the Fe moment, F = (sin θ cos φ, sin θ sin φ, cos θ) at a given site, we must project the added electrons onto the allowed direction to satisfy Pauli exclusion, locally setting f ↑ = sin θ 2 e −iφ/2 f and f ↓ = − cos θ 2 e iφ/2 f , effectively "stripping" the electron of its spin degree of freedom. Such models have been proposed for other DP materials, [3][4][5][6][7][8]10,11 and shown to capture the phenomenology of Sr 2 FeMoO 6 including thermal phase transitions and disorder effects. [37][38][39] However, most of these previous studies, with the notable exception of Ref.…”
Section: Modelmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] Insulating variants where only the B'-site ion is magnetic, such as Ba 2 YMoO 6 and La 2 LiMoO 6 , provide material examples of quantum mechanical moments living on the geometrically frustrated face-centered cubic lattice. [12][13][14][15][16] Metallic DPs, such as Sr 2 FeMoO 6 , are also of significant technological importance, being room temperature ferrimagnets with half-metallic band structures and a large spin polarization which is useful for spintronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…9 It has been suggested that the magnetic temperature T c , and whether the ground state is metallic or insulating, vary as A is changed from Ba to Sr to Ca. 10 Also mis-site disorder may have pronounced effect on the magnetic properties of these compounds. 11,12 Recent experiments 13 have established in Sr 2 FeMoO 6 an electronic structure and configuration of five localized majority electrons (high spin state) on Fe and one delocalized electron shared between Mo and the other sites.…”
Section: Introductionmentioning
confidence: 99%